The Effect of Student Team Achievement Divisions Model Assisted with Geogebra Media on Understanding of Mathematical Concepts of Circle Materials in Class VIII Students of SMP Muhammadiyah 1 Purwokerto - Desya Adella Nur Afinda (Faculty of Tarbiya and Teacher Trainning, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2023)
This research was conducted based on the low ability to understand mathematical concepts of students in class VIII SMP Muhammadiyah 1 Purwokerto. One of the contributing factors is the use of inappropriate learning models. The solution that is considered capable of increasing the ability to understand mathematical concepts is to apply the STAD learning model assisted by Geogebra media in the learning process. The STAD learning model is a cooperative type learning model that is carried out by forming small groups according to students' abilities, then students are encouraged to help each other in understanding the material, so that later students are able to do individual quizzes well and get high scores, which scores are effect on the final score of the group. Geogebra is a dynamic mathematical software that facilitates users to visualize or demonstrate and construct mathematical concepts interactively. This study aims to determine whether there is an influence of the STAD model assisted by geogebra media on the ability to understand mathematical concepts in class VIII students of SMP Muhammadiyah 1 Purwokerto. The type of research used is quantitative with experimental research methods. The population in this study were all students of class VIII SMP Muhammadiyah 1 Purwokerto, totaling 118 students with a sample of 38 students, 24 students from class VIII B and 14 students from class VIII D. The research variables were the STAD model assisted by geogebra media as the independent variable and ability to understand mathematical concepts as the dependent variable. Methods of data collection is done by observation and tests. Data analysis using the t test. The results showed that there was an influence between the STAD model assisted by GeoGebra media on students' ability to understand mathematical concepts.